Ecofren Enterprise - Nasir, M. Amali; Jahnatan, Sherly; Jakius, Liliana; Jelin, Sofrih (2014)
First section of our business plan will be the introduction of our business, the introduction include the purpose of our business plan. The background of business and partners, business logo, vision , mission and objective and also the partners agreement. This section in important to give a simple representation to the leader about our business plan. second section of our business plan will be the administration plan. This section is important to assist us in our business administration. The good business administration can help to maintain the efficiency of business operation. This administration plan will explain the task of every partner and also the workers in this business. It also provide the organization chart to show the hierarchy of management in our business. Besides, it also explain the incentives that we provide for our worker. Third section of our business plan will be the marketing plan. Marketing plan will emphasize on the strategies to market our product. The proper strategies can help to increase our sales and also attract more customers . Besides, marketing plan also will show the targeted market as well as the market share before and after we enter the market. In addition we also identifying the strength and weakness of our competitors in this marketing plan in order to compete with them Fourth section of our business plan will be the operational plan. The operational plan will clarify the operation of our business. It will show the process that involve in our business operation. Besides, it also will point up the production budget for our business. Operational plan is important to ensure that we can run our business operation smoothly. The last section of our business plan is the financial plan. Financial plan is important to determine the capital needed as well as the source of finance to implement our business. This section will show the budget from the other three sections , the fixed asset and also the financial performance of our business. The financial plan also important to appraise the viability of our business before the actual investment is committed.